Depressive-like phenotype enhances relapse of nicotine seeking after forced abstinence in rats - Amchova, Petra; Ruda-Kucerova, Jana (The world journal of biological psychiatry, 2023)
OBJECTIVE: Comorbidity of depression and drug addiction is common, but effective treatment is missing. A rat model combining the olfactory bulbectomy (OBX) model and IV drug self-administration has provided evidence of differential reactivity of the OBX rats towards drugs of abuse. This study evaluates nicotine taking and seeking behaviour in this model. METHODS: Adult male Wistar rats were used; in one group, the OBX was performed while the other group was sham-operated. After three weeks of nicotine self-administration (fixed ratio-1 schedule), rats underwent two weeks of forced abstinence followed by a drug-free relapse-like session. Two doses of nicotine were studied: 0.019 and 0.030 mg/kg per infusion. The locomotor test took place before the self-administration protocol and on the first day of abstinence. RESULTS: OBX induced characteristic hyperactive locomotor phenotype. OBX rats self-administered more nicotine in the experiment using 0.019 mg/kg per infusion, but they reached lower drug intake in the study using 0.030 mg/kg per infusion. However, relapse of nicotine seeking after forced abstinence was significantly higher in the OBX groups in both cohorts. CONCLUSION: These results are in line with previous studies showing OBX-induced dissimilarities in drug-seeking and drug-taking and represent complementary information to reports on other substances.
Keywords: potkani Wistar; recidiva; Recurrence; autoaplikace; Rats; bulbus olfactorius; Olfactory Bulb; Nicotine; Animals; Phenotype; krysa rodu Rattus; Rats, Wistar; mužské pohlaví; Male; Self Administration; nikotin; fenotyp; zvířata